EVALUATION OF ATTITUDES OF THE STUDENTS TOWARDS LIFELONG LEARNING. - SARIGÖZ, Okan; DEMİRALAY, Raziye (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2015)
This research's purpose is to determine the students' attitudes towards Lifelong Learning. In the study, 'General Screening Model' which is one of the descriptive methods was used. The sample of the research constitutes 814 students studying in Adana Vocational School at Çukurova University in 2015-2016 school year. According to the results obtained from the research, it was determined that the students express themselves better in their mother tongue and do not always look positively and constructively at developing societies. Furthermore, such results have been reached in the research that there is no a statistically significant difference of opinion between the students in the 1st grade and in the 2nd grade depending on the variable of class level.